Percobaan Pembangunan Partisipatif dalam Otonomi Daerah - Agusta, Ivanovich (Sodality: Jurnal Sosiologi Pedesaan, 2009)
As part of governing mechanism, local participation has already been practiced by numerous ethnic groups of Indonesia since centuries. In modern era, the idea of participation, that was at the outset integrated into development thought as desentralisation, was introduced in 1950s-1960s. In the 1980s, Non-Government Organization adopted participatory development to control government and donor agencies. Since 1990s, donor and developed countries adopted paticipatory development as single approach to operationalize development measures. In Indonesia, participatory development practices need to pay attention on two sub-structures, i.e., program and budget arrangements. Musyawarah Perencanaan Pembangunan (musrenbang) is a participatory-based planning mechanism is run stretching from rural upto national level and is considered to be very central for nation-wide development measures. The mechanism needs to be criticed since it just increases efficiency and effectiveness of development actions, but it fails to expand participaton space of the lowest social layers of rural communities